EFEK KOMUNIKASI MASSA DALAM DAKWAH QURAISH SHIHAB TENTANG ISLAM WASATHIYYAH - Wahyu Setiawan (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2021)
Da'wah through mass communication such as that done by Quraish Shihab through Najwa Shihab's Youtube channel has attracted attention so that many viewers who saw this show reached more than one million. There must be a mass communication effect in the da'wah. This study examines the extent of the effect of mass communication that is formed on the audience who watch this da'wah program. This study uses a qualitative method with a descriptive type, the primary data source is the Najwa Shihab Youtube channel, the data collection technique is through documentation, namely from the Quraish Shihab Youtube propaganda video about Wasathiyyah Islam, Islam in the middle. Data analysis used the Miles and Huberman model. The findings in this study are the effect of mass communication with the process formed through prosocial cognitive, there is an image formed on Quraish Shihab and there is also an affective effect of mass communication with the process formed because of the image formed on the information or knowledge possessed of certain objects and also formed from cognitive schema processes